Defining Moments, Revisited. Issue 8 (3rd July 2021) - Beach, Wayne A.
ABSTRACT: 'Defining moments' are revealed by weaving three strands together in this essay. First, by reenacting stories as 'tell-aboutables, ' 'defining moments' are achieved through participants' methods for drawing attention to significant events. Occasioned reconstructions are designed by speakers as timely and worthy to be heard, responded to, and appreciated by recipients. In turn, 'defining moments' of shared existence emerge through next stories, serial orderings of storytelling achievements exposing (in Goffman's terms) less about people and their moments than moments and their people. Second, numerous examples are provided of how stories about cancer comprise altogether routine everyday life activities for patients, family members, and providers. 'Defining moments' can and do become radically re-defined when landscapes of wellness give way to progressive entanglements and forfeitures of sickness. When 'health' comes into play, it is not uncommon for priorities to be given less to self-promotion (e.g. blaming and boasting), and more to efforts designed to optimize mental, emotional, spiritual, and physical well-being. Third, personal stories about 'defining moments' are shared from my long-term investigations of family cancer and patient–oncologist interactions. A vibrant reflexivity is cultivated when we recognize that, and how, our basic research can be successfully translated to advance the public good.